The diplomacy of King Jugurtha (118-105 BC) (مجلة الواحات للبحوث والدراسات, 2025)
Many topics related to ancient history are still influenced by the perspectives inherited from colonial interpretations. This has contributed to the ambiguity in the views of historians who only saw ancient kings as mere warriors, overlooking their diplomatic roles. This trend can be observed from Masinissa to Jugurtha. While Jugurtha is often portrayed in sources as a prince of war, his diplomatic acumen is often overlooked. Jugurtha delved into diplomatic efforts before war against Rome, aiming to find solutions avoid warfare. However, the situation took a different turn when Roman forces targeted him in 111 BC following the events in Cirta in 112 BC. Despite the war between the years 111-105 BC, Jugurtha's diplomacy continued with his neighbor Bocchus I to keep Rome at bay from Numidia. The main issue of the article was as follows: What was the diplomatic role played by Jugurtha during his reign from 111-105. BC?Keywords: Jugurtha, diplomacy, Numidia, Rome.